ANALYSIS OF THE RELATIONSHIP BETWEEN SERVICE QUALITY AND PATIENT SATISFACTION IN POLYCLINIC ACUPUNCTURE AND HERBS LKTM PALEMBANG - Maulana, Nurehan; Novianti, Leni; Sutriyati, Sutriyati (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2021)
Background: Satisfactory and quality service will form patients/customers loyalty, and satisfaction is very closely related to word of mouth. The next effect will continue on the process of forming an improved image of health care agencies. The standard of patient satisfaction in health services is set nationally by the Ministry of Health at a minimum for patient satisfaction, which is above 95%. The purpose of this study is to find out the relationship between the quality of service in aspects of staff attitude, service facilities, and rates/fees with patient satisfaction in polyclinic acupuncture and herbal LKTM Palembang. Methods: This research is quantitative and uses an analytic survey with a cross sectional design. The sample in this study were all patients of the Palembang Community Traditional Health Workshop (LKTM) in 2020 who visited during the study period, numbering 85 people. Result: Based on the results of the study, 62.4% expressed satisfaction with the services in Polyclinic Acupuncture and Herbs (LKTM). The dimension that needs to be improved is the Assurance dimension in the officer's capability section. Based on the result of Chi-Square statistical test, the level of patients satisfaction to the service attitude of the officer, with a p-value of 0.000. Recommendation: for LKTM Palembang, it is expected to improve the quality of existing health workers and always play an active role in health services, maintain existing facilities, and review the costs set.